2019
DOI: 10.3390/antiox8110510
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Accumulation in Black Kernel Mutant Rice and its Contribution to ROS Detoxification in Response to High Temperature at the Filling Stage

Abstract: Effect of high temperature (HT) on anthocyanin (ANS) accumulation and its relationship with reactive oxygen species (ROS) generation in color rice kernel was investigated by using a black kernel mutant (9311bk) and its wildtype (WT). 9311bk showed strikingly higher ANS content in the kernel than WT. Just like the starch accumulation in rice kernels, ANS accumulation in the 9311bk kernel increased progressively along with kernel development, with the highest level of ANS at kernel maturity. HT exposure evidentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Therefore, most literature reviews tend to focus on the roles of anthocyanins in enhancing tolerance to abiotic and biotic stresses. Zaidi et al, 2019 showed that high temperature during grain development resulted in declines in grain weight and kernel starch content, and a mutant rice plant displaying grain anthocyanin production was much less damaged by high temperatures compared to wild-type plants without grain anthocyanin pigmentation [ 146 ]. In addition, anthocyanin has been used to distinguish drought-responsive traits.…”
Section: Significant Roles Of Anthocyanin From Purple Rice In Human Healthmentioning
confidence: 99%
“…Therefore, most literature reviews tend to focus on the roles of anthocyanins in enhancing tolerance to abiotic and biotic stresses. Zaidi et al, 2019 showed that high temperature during grain development resulted in declines in grain weight and kernel starch content, and a mutant rice plant displaying grain anthocyanin production was much less damaged by high temperatures compared to wild-type plants without grain anthocyanin pigmentation [ 146 ]. In addition, anthocyanin has been used to distinguish drought-responsive traits.…”
Section: Significant Roles Of Anthocyanin From Purple Rice In Human Healthmentioning
confidence: 99%
“…High temperature induces an alteration in the expression of CHS, F3H, DFR, and ANS genes in rice and hinders anthocyanin synthesis, resulting in decreasing accumulation of anthocyanin in the rice caryopsis. A daily mean temperature of about 32 °C compared to that of 22 °C can result in a reduction of more than 20% in the amount of anthocyanin during grain filling [ 138 ]. Kim and co-workers [ 69 ] reported that the expression level of CHS, F3H, DFR, ANS, and AN5 of the Heugjinju black rice cultivar was 200–500-fold lower for plants grown under 21 °C compared to those grown under 27 °C.…”
Section: Enhanced Anthocyanin Accumulation In Rice Caryopses Throumentioning
confidence: 99%
“…A positive correlation was also observed between OsC1 expression and late ABP genes. Transcript abundance of F3H, DFR and ANS have been reported in colored rice variety compared to white rice variety at 7 DAP (Kim et al, 2007;Zaidi et al, 2019). We also speculate that OsC1 could be an activator of anthocyanins/flavonoids-related genes such as F3 0 H/DFR/ANS.…”
Section: Overexpression Of Osc1 Impacts On Abp Modulationmentioning
confidence: 61%